Examining the Global Climate Change Crisis: A Critical Analysis of Roy Bhaskar’s Meta-Reality and the Ontology of Islamic Law - Fidelis Oktovianus Sanbein; Siti Murtiningsih; Lailiy Muthmainnah (Universitas Islam Sultan Agung, 2026)
Purpose – The global climate crisis can no longer be understood merely as an ecological issue; rather, it is a structural manifestation of fossil capitalism that reproduces social inequality, environmental exploitation, and humanity's ontological alienation from nature. This article aims to analyse the climate crisis through the reciprocal relationship between Roy Bhaskar's concept of Meta-Reality and the ontology of Islamic law, whilst formulating an Islam-Metarealist framework as a transformative ecological paradigm.Methodology/approach - This research is a qualitative study grounded in a literature review, employing an approach informed by Islamic legal philosophy and critical realism. Data were collected through documentary research and a critical examination of the works of Roy Bhaskar, literature concerning climate justice and fossil capitalism, as well as studies on Islamic environmental jurisprudence (fiqh al-bī'ah), Islamic legal theory (uṣūl al-fiqh), and the objectives of Islamic law (maqāṣid al-syarī'ah) in relation to the environment. Analysis was conducted using philosophical hermeneutics, normative discourse analysis, and critical retroduction to elucidate the causal structure of the climate crisis.Findings - The results indicate that the climate crisis represents a manifestation of fossil capitalism's demi-reality, which normalises ecological exploitation through the logic of unlimited growth. In contrast, the principles of the oneness of God (tawḥīd), stewardship (khilāfah), and trustworthiness (amānah) offer an ontological foundation for equitable and sustainable climate governance. The Islam-Metarealist framework synthesises the causal-structural analysis of critical realism with the Islamic normative horizon to critique fossil capitalism on both ontological and moral grounds.Conclusion – This research highlights the necessity of reinforcing ecological juristic reasoning (ijtihād) within religious authorities, Islamic educational institutions, and the formulation of public policy. Furthermore, the climate crisis has been demonstrated to have significant social ramifications, including the exacerbation of socio-ecological inequality, the marginalisation of vulnerable groups, conflicts over resources, as well as the erosion of intergenerational justice and ethical disorientation in humanity's relationship with nature. Consequently, the energy transition must be perceived as a social justice agenda that prioritises not only emissions reduction but also the protection of vulnerable communities, the restoration of social cohesion, and the reconstruction of society's moral orientation. The response to the climate crisis should be directed towards institutional reforms that are more just, participatory, and intergenerationally responsible, whilst also restoring humanity's ontological connection with nature as part of a divine mandate.